Use of Information Sources on Vaccine-Preventable Diseases in Pregnant Women: An Experience in Ferrara, Italy - Giovanni Gabutti (International Journal of Environmental Research and Public Health, 2019)
The “vaccine hesitancy” and the consequent lowering of vaccination coverage have, on one hand, pushed the Italian government to reintroduce some new compulsory vaccinations for access to schools and, on the other, have imposed a greater effort on health operators to understand the causes and, consequently, to intervene with tools for promotion and health education. In Ferrara, we administered 201 non-self-filling questionnaires to 201 pregnant women within a cross-sectional multicenter study, consisting of 63 items divided into 7 sections. In particular, we wanted to investigate the correlation between the socio-demographic characteristics of the interviewees and the sources used to obtain information and, on the other side, the intention to vaccinate in relation to the perception of the diffusion and of the risk of vaccine-preventable diseases. The institutional information sources are less used by foreigners, primiparous, and women with a low education level. The perception of the severity of vaccine-preventable diseases was greater in those inquiring from institutional sources. In a public health perspective, knowing the profile of future mothers in terms of socio-demographic characteristics and of the quality of the used information channels may help to guide the choices of communication in the vaccination field.